University Students’ Perception of Relationship Marketing Tactics and Its Impact on Service Utilization of Global System for Mobile Communication - Adu, Richard Akinjide; Shenge, Nyitor Alexander; Ojo, Solomon; Olonade, Zaccheaus Olufunminiyi; Adegbite, Sanya Obasonjo (Journal of Information Systems Research and Practice, 2024)
Nigeria telecommunication industry had grown tremendously beginning from 2001 when three service providers namely; MTN, ECONET (now Airtel) and MTEL, were awarded the Global System for Mobile Communication (GSM) license in January 2001. The growth rate has necessitated the need to engage in marketing strategies that would help the GSM operators attract new customers and as well keep their present customers loyal. Although, there is no agreement on factors influencing GSM service utilization. Against this background, this study examines influence of customer perception of relationship marketing tactics on global system for mobile communication service utilization. The specific objective was to determine main and interaction influence of relationship marketing tactics on GSM service utilization. Compared to previous research, this study breaks new ground by investigating influence of such fundamental relationship marketing tactics; customer trust, brand image, service quality, promotion/value offered, and price perception as measures of GSM service utilization. The study utilized cross-sectional survey design that covered 710 participants, male; 55.9% and female; 44.1% undergraduate and postgraduate students of the University of Ibadan, Nigeria. All the instruments employed for data collection were valid and reliable and with Cronbach’s alpha of 0.75 and above. The results revealed that service quality had a significant main influence on service utilization i.e. F (1,675) = 24.71; with P < .05. Customer trust had a significant main influence on service utilization i.e. F (1,675) = 29.26; with P < .001. Likewise, promotion/value offered and customer trust had a significant interaction influence on service utilization i.e. F (1,675) = 5.81; with P < .05. This research confirmed the external validity of similar findings in the West and demonstrated the generalizability of relationship marketing tactics as influencers of GSM service utilization.